ON TRAINING OF COMPETITIVE PERSONNEL - ON THE BASIS OF CREATING A NEW GENERATION OF TEACHING LITERATURE IN THE EDUCATIONAL PROCESS (in the example of mechanical science) - Mamajanov, Shavkatjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article presents practical research results and corresponding recommendations by creating the literature of a new generation, in the education system that should be carried out so that students become mature specialists in their chosen fields. Objective. Currently, there is a strong need to study the problems of students and professors working with educational and scientific literature in the higher education institutions. to develop some methodological recommendations based on the obtained results. This article is written as a practical expression of this goal. Methods. Almost no research has been done in this regard. Based on this aspect, it was found appropriate to research this issue on a scientific basis, to develop some methodological recommendations based on the obtained results. This article is written as a practical expression of this goal, and it also contains a number of recommendations. Results. Based on the above requirements, there are a lot of aspects that can be studied in foreign literature and can be used in the creation of a new generation of literature in the Uzbek language. Teaching and scientific materials would be perfectly written - all the pictures, drawings and graphs used would be colorfully described in a simple and understandable way, and each elementary part is explained in detail